2013
DOI: 10.1186/1748-717x-8-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in marginal zone lymphoma

Abstract: PurposeTo evaluate the efficacy of radiotherapy (RT) for early-stage nodal and extranodal marginal zone lymphoma (MZL).Materials and methodsPatients with stage I (n = 22) and stage II (n = 8) MZL, who were treated with RT were reviewed. The primary tumor localisation was in the orbita (n = 12), stomach (n = 8), head and neck other than the orbita (n = 8), breast (n = 1) and one case of marginal zone lymphoma of the skin (n = 1). The median radiotherapy dose was 40 Gy (5 to 45 Gy).ResultsThe median follow-up ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[10] So local therapy alone, either surgery or radiotherapy, may be curative. [11] Deinbeck et al, [12] treated 30 marginal zone lymphoma patients with median 40 Gy of radiation. Ninety percentage of these patients had extranodal presentation, and there was no infield recurrence after median 103 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[10] So local therapy alone, either surgery or radiotherapy, may be curative. [11] Deinbeck et al, [12] treated 30 marginal zone lymphoma patients with median 40 Gy of radiation. Ninety percentage of these patients had extranodal presentation, and there was no infield recurrence after median 103 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have suggested radiotherapy to play the same role 11. Deinbeck et al 12 reported to have cured 30 patients with marginal zone lymphoma with 40 Gy of radiation. Ueda et al 13 reported extraintestinal MALT lymphoma to have a worse prognosis with multiorgan involvement than gastric MALT lymphoma, even after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Brachytherapy has advantages over EBRT in the dose distribution to OARs, and previous RT plan studies that tried to mimic the dose distribution of brachytherapy by IMRT and proton beam demonstrated that EBRT plans were inferior to brachtherapy plans [ 19 ]. Although several studies did not report severe late toxicities [ 12 , 13 ], these studies usually had a short follow-up period with a small number of patients, making them less representative. A recent prospective phase II study reported a 2-year cumulative grade 3 or worse toxicity rate of 26.7%, which was predominantly rectal, and two of the patients had grade 5 fistula formation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%